(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with the treatment costs of heart failure at Le Van Thinh Hospital. Methods: A cross-sectional descriptive study was conducted using retrospective data from 2,386 treatment episodes of heart failure in 2024. Multivariate linear regression analysis was applied to determine cost-related factors, with the dependent variable being the total treatment cost per episode (log-transformed). Independent variables included age, sex, type of treatment, length of stay, and specific health conditions (atrial fibrillation, stent placement, diabetes mellitus, chronic kidney disease). Results: The study sample consisted of 2,226 outpatient episodes (93.2%) and 160 inpatient episodes (6.8%). The mean cost per outpatient treatment was 794,000 ± 321,000 VND, while the median cost per inpatient treatment was 5,353,000 VND. Medications accounted for 85.8% of outpatient costs and 37.8% of inpatient costs. The multivariate linear regression model (R² = 0.847) indicated that higher costs were associated with inpatient treatment (+179.4%), stent placement (+16.5%), heart failure with type 2 diabetes (+30.3%), and each additional day of hospitalization (+21.9%). Conclusion: Treatment costs of heart failure can be estimated based on patients’ specific health conditions, which may support financial planning and cost management.